Evaluation of the periodic table as a teaching tool and content for conceptual change in chemical processes - Mhlongo, Thabo; Sedumedi, Thomas Dipogiso (Journal of Science and Education (JSE), 2023)
This study focused on two crucial chemistry concepts, chemical bonding and related reactions. It explored how learners may conceptually use the periodic table in their scientific understanding. Specifically, the study's goal was to ascertain the effect of the use of this tool on learners' conceptual knowledge and/or reasoning abilities during learning or knowledge construction. The study utilized qualitative methodology and was based on a case (the school). For the purposes of the experiment, the participating learners—learners in grade 11 chemistry—were split into two groups (control group and experimental group). The study's findings indicate relationships between learners' knowledge (re)construction of chemical processes and their applicability to the periodic table. Future research is suggested by the researchers on the links between learning conceptual change and teaching approaches using the periodic table.